Islamic Social Environment Perspective and Intention Decisions of Accounting Students at Islamic Financial Institutions - Ananda Setiawan (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2021)
The aim of this research is to test the Islamic social environment on interest decisions and tests from a psychologically behavioural perspective rooted in the theory of planned behaviour (TPB) in individual interest decisions. The research method uses structural equation modeling (SEM) through SmartPLS 3.0 software, with a sample of 157 accounting students at state universities (PTN), state Islamic religious colleges (PTKIN) and private universities (PTS) located in Central Java, West Java and East Java, Yogyakarta. The test results showed that the Islamic social environment significantly affects interest decisions, theory of planned behaviour (TPB) which has dimensions of attitudes, subjective norms and perceptions of behavioural control have a significant effect on islamic social environment and interest decisions. Meanwhile, attitude and subjective norms point to a significant direction toward interest decisions through islamic social environments, while perceptions of behavioural control are insignificant over decisions